Perbandingan Sistem Pendidikan Negara Cina dan Indonesia: A Comparative Study of the Educational Systems of China and Indonesia - Yuliana, Elfa (Lembaga Bale Literasi, 2025)
This study aims to identify the differences and advantages of the education systems between China and Indonesia. The method used in this research is a literature study or library research. The findings reveal that the structure of education in China begins with a three-year preschool level, which means formal education starts when children are around three years old. At the age of six, children then enter the elementary school level. China also provides special education programs for children with exceptional abilities, allowing them to skip grades based on their performance. At the higher education level, China has experienced rapid development and various reforms over the past decade. Chinese higher education offers two main pathways: academic programs and vocational programs.